Adição de cinza da lenha de algaroba (Prosopis juliflora) em massa cerâmica para revestimento - Santos, Leonardo Leandro dos (2014)
It is estimated that there are 500,000 acres of mesquite (Prosopis juliflora) planted in the Brazilian Northeast, 45% only on State of Paraíba. In State, the wood is used almost exclusively as fuel on drying kilns and firing of ceramic products in brick kilns, generating ash as residue. These ashes contain a high concentration of alkaline metals and earth metals, mainly CaO and K2O. This work studies the use of this residue in the ceramic tiles industry, in substitution to the feldspar. Thirteen mixtures with equal ratios of clay, kaolin and quartz, and the residue (varying from 5% to 20%, still under three granulometric perspectives), and prepared specimens of dimensions 110 mm x 55 mm x 8 mm in uniaxial tool die, with compacting pressure of 15 MPa. The samples were fired in three different temperatures: 1160°C, 1190°C and 1220°C, during 20 minutes, and characterized by means of X-ray fluorescence, X-ray diffraction, gravimetric thermal analysis and differential thermal analysis. The results of water absorption, apparent porosity and specific mass, linear shrinkage and flexural strength were also analysed. The specimens with addition of 5 and 10% ash, of granulometric -#35 +#60 (250 μm < particle size < 500 μm), fired in 1220°C, presented results of water absorption of 0.99% and 0.62%, respectively, which according to the ABNT, ASTM and ISO standards can be classified as stoneware tiles, and flexural strength of 23.3 and 23.0 MPa, respectively, being classified as coating materials.